LABORATORY FINDINGS IN PSORIATIC ARTHRITIS - S. Todesco; R. Ramonda; V. Modesti; A. Lonigro; F. Oliviero; M. Poswiadek; L. Punzi (PAGEPress Publications, 2011)
Psoriatic arthritis (PsA) has been classically defined as an inflammatory arthritis associated with psoriasis. However, in comparison with other relevant inflammatory arthropathies, in which a definite diagnosis is frequently possible only by means of laboratory investigations, in PsA true laboratory diagnostic markers are lacking. Some markers are utilised more to differentiate other diseases than to characterise PsA. For example in polyarticular PsA, which may be in some cases indistinguishable from RA, the rheumatoid factor (RF) or the more specific and recently introduced antibodies to cyclic citrullinated peptides (anti-CCP), may be useful to better identify RA. However, RF was found in 5% to 13% of patients with PsA, and anti-CCP may be observed in almost similar percentage. The determination of ESR and/or CRP is frequently disappointing in PsA, since they are both elevated in only half of the patients with PsA. However, ESR and/or CRP are included in the most utilised response criteria for RA, such as ACR and DAS, and, in addition are also considered reliable in the assessment of PsA. Furthermore, elevated levels of ESR have been proposed as one of the best predictors of damage progression and, in addition, a low ESR seems protective, while an ESR >15 mm/h is one of the factors associated with an increased mortality in PsA. The synovial fluid (SF) effusion is much higher in PsA, in comparison with other arthropathies. When available, SF analysis may offer additive information useful for the diagnosis, such as the increased number of leukocytes, which underlines the inflammatory nature of the effusion even in a patient with normal serum levels of acute phase response. We found that elevated IL-1 levels in SF of patients with early disease (<6 months), may be predictive of an evolution in polyarticular form at follow-up. This observation is in keeping with the crucial role that inflammatory cytokines play in PsA, probably related to a genetic predisposition. The recent introduction in PsA of anti-TNF-α agents and the demonstration of their efficacy in the management of many clinical disease expressions including peripheral arthropathy, axial involvement, enthesopathy and skin manifestations, have stimulated the research also in the field of the possible laboratory markers. Key words: Psoriatic arthritis, laboratory investigations arthritis